Dan O'Quinn in his favourite chair in the living room - O'Quinn, Kathleen (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Floor Plan and Survey of Three Rooms on Ground Floor. Kitchen, Living Room and Dining Room of Dan O'Quinn's Home, West Bay, Port-au-Port, Newfoundland ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Floor Plan and Survey of Three Rooms on Ground Floor. Kitchen, Living Room and Dining Room of Dan O'Quinn's Home, West Bay, Port-au-Port, Newfoundland"